Analisis Langkah-Langkah Preventif Yang Dapat Diambil Oleh Content Creator Ketika Hak Orisinalitas Di Langgar Dalam Konten Video - Pandito Malim Hasayangan Tanjung; Zalzabila Agnia Husna (Lembaga Pengembangan Kinerja Dosen, 2024)
In the rapidly evolving digital age, video content has become one of the dominant and popular forms of communication. However, with the ease of access and dissemination of content, the risk of originality rights infringement has become increasingly high for content creators. This research aims to analyze the preventive measures that content creators can take when their originality rights are violated in video content. The research method involves analyzing the policies and features of major platforms such as YouTube and TikTok, as well as a review of the concept of copyright in applicable laws. The analysis shows that content creators can take effective preventive measures, including copyright registration, the addition of clear watermarks, active monitoring of content usage, and cooperation with platforms. While challenges remain, consistent preventive efforts and copyright awareness can help content creators protect their original works in the dynamic digital realm. This research provides practical guidance for content creators to maintain the integrity of their creativity and encourage a culture that respects originality rights in the digital environment.